2017
DOI: 10.1111/lam.12745
|View full text |Cite
|
Sign up to set email alerts
|

Effects of culture conditions on the size, morphology and wet density of spores ofBacillus cereus569 andBacillus megateriumQM B1551

Abstract: Significance and Impact of the Study: Bacterial spores of the genera Bacillus and Clostridium represent nature's most durable cells in terms of their extreme resistance to a variety of deleterious environments. As a result, they are of concern in the food processing, healthcare and other sectors, and are of increasing biotechnological interest. Improved understanding of variance in spore size, morphology and density may aid the development of certain spore-associated applications (e.g. spore surface display) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…This may be a result of the large exosporium present in B. cereus spores, which may provide a greater number of sites for the adsorption of manganese ions. The average exosporium surface area of B. cereus spores is approximately 25% larger than that of B. megaterium spores (Xu Zhou, Wisnivesky, Wilson, & Christie, ).…”
Section: Resultsmentioning
confidence: 99%
“…This may be a result of the large exosporium present in B. cereus spores, which may provide a greater number of sites for the adsorption of manganese ions. The average exosporium surface area of B. cereus spores is approximately 25% larger than that of B. megaterium spores (Xu Zhou, Wisnivesky, Wilson, & Christie, ).…”
Section: Resultsmentioning
confidence: 99%
“…Competent Escherichia coli DH5␣ cells (NEB UK) were used for cloning procedures and for the propagation of plasmids. Bacillus cereus spores were prepared by nutrient exhaustion in casein-hydrolysate yeast-extract (CCY) liquid medium (24). Efficient sporulation was achieved using 200-ml cultures in 2-liter baffled flasks that were subject to orbital agitation at 30°C for 48 h. The resultant spores were purified from cellular debris by centrifuging and resuspending the spore pellets initially in phosphate-buffered saline (PBS) supplemented with 0.1% (wt/vol) Tween 20, followed by several rounds of washing and resuspending spores in ice-cold deionized water.…”
Section: Methodsmentioning
confidence: 99%
“…; Xu Zhou et al . ). Maximum protease production for both B. subtilis and B. licheniformis was reached at 40°C with an optimum pH of 6·0–6·5 (Ray et al .…”
Section: Optimum Cultivation Conditions For Metabolite Productionmentioning
confidence: 97%
“…A number of studies have investigated the influence of cultivation conditions on Bacillus spore production (Posada-Uribe et al 2015;Xu Zhou et al 2017), while others focused on conditions for optimum protease production (Ray et al 2012;Sarker et al 2013). It was found that alkaline media and elevated temperatures reduced the volume of spores, while aeration and agitation rates affected spore cell density (Posada-Uribe et al 2015;Xu Zhou et al 2017). Maximum protease production for both B. subtilis and B. licheniformis was reached at 40°C with an optimum pH of 6Á0-6Á5 (Ray et al 2012).…”
Section: Optimum Cultivation Conditions For Metabolite Productionmentioning
confidence: 99%